KETAHANAN KELUARGA DAN POLA RELASI GENDER SAAT WORK FROM HOME DI TENGAH PANDEMI COVID-19 - Nawa Syarif Fajar; Miftahus Sholehudin (Raheema, 2022)
Corona outbreak, which in 2019 infected one of the cities in China, became a global outbreak in 2020. Various countries issued extraordinary policies in response to and handling of the virus by WHO named Coronavirus Disease 2019 (in the future referred to as COVID-19). The policies of various countries of the world, including Indonesia, have an impact on all social strata of society, including families and members in the family of both children, wives, and husbands. Perspective justice and gender equality is fundamental to study the application and function in shaping family resilience. Family resilience becomes very important in overcoming various problems in the household, not only at this time but will have far-reaching implications for the children's future in mentally preparing their lives. With a normative approach, this study unearthed literature data that illustrates the urgency of family resilience during the implementation of the work from home program in Indonesia. This study concludes that the role of the family in realizing family resilience is essential. However, more than that, gender awareness and justice applied in the household is a necessity because of children who, as family members who grow up with injustice or gender discrimination, will color their mindsets and behavior. In addition to the family, the government has the maker of regulations and policies for dealing with outbreaks is also expected to use a gender lens so that various outbreak management programs do not harm one particular gender.